The intrinsic value of decision rights - Björn Bartling; Ernst Fehr; Holger Herz (University of Zurich, Department of Economics, 2013)
Philosophers, psychologists, and economists have long argued that certain decision rights carry not only instrumental value but may also be valuable for their own sake. The ideas of autonomy, freedom, and liberty derive their intuitive appeal - at least partly - from an assumed positive intrinsic value of decision rights. Proving the existence of this value and measuring its size, however, is intricate. Here, we develop an experimental method capable of achieving these goals. The data reveal that - across different parameterizations - the large majority of our subjects intrinsically value decision rights beyond their instrumental benefit. The existence of an intrinsic value of decision rights helps understand the allocation of decision rights in practice, and it has implications for their optimal allocation in organizations, economic institutions, and society at large.
Keywords: C91; D03; D23; 330; decision rights; intrinsic value; authority; Motivation; Soziale Werte; Autorität; Entscheidungstheorie; Test